Diasporic Belonging in Religious Spaces: Insights from Within the Sri Lankan Diaspora - Ratnam, Charishma (Journal of intercultural studies, 2024)
The changing social, cultural and physical characteristics and uses of public spaces by migrants are of longstanding interest to social scientists. Often embedded in uses of public spaces are splinters, resonances and connections to home and migration. This paper examines the religious spaces that Sri Lankan migrants engage with in Sydney and Melbourne, Australia. To untangle the complexities associated with these spaces, we integrate a framework of belonging that encompasses rituals, relationships and restrictions. A multilayered dataset, which includes interviews with the Sri Lankan diaspora, (auto)ethnography, field observations and photography, revealed that within the Sri Lankan diaspora, individuals often used religious spaces to maintain rituals and identities. The data uncovered that some participants in the diaspora used religious spaces to gather and socialise with other diaspora members while others had dynamic relationships with these spaces – that is, the meanings attributed to religious spaces were at times fraught with tensions and hostilities towards religious practice and feelings of welcome. In this paper, we offer a snapshot of a growing diaspora in Australia and their negotiations to belong (or not).